Ideal victim and competition for victimhood in the stories of the survivors of the war in Bosnia and Herzegovina - Bašić Goran (Temida, 2015)
Previous research on victimhood often presented a one-sided picture of the “victim” and the “perpetrator”. Researchers have emphasised the importance of narratives and they have focused on narratives about victimhood, but they have not analysed post-war interviews as an arena for the competition for gaining the status of victim. This paper tries to fill-in this gap through analysing stories of 27 survivors of the war in Bosnia and Herzegovina during the 1990s. The paper aims at describing the interviewees’ portrayal of “victimhood” as a social phenomenon, as well as to analyse those discursive patterns, which contribute to constructing the categories of a “victim” and a “perpetrator”. The research question is: How do the interviewees describe victimhood after the war? Within the dynamics that constructs the status of a “victim” and a “perpetrator” a competition for the role of a victim is noticeable after the war. All interviewees are eager to present themselves as victims, while at the same time they diminish the victim status of other categories. This situation can produce and reproduce competition for gaining the status of a victim, and, in this way, to reinforce collective demarcations that were played out so successfully during the war.